Variasi Suhu Pemadatan Campuran AC-Base Menggunakan Batu Sungai Seriti, Kabupaten Luwu - Sandhika Yuda Panggara; Alpius; Louise Elizabeth Radjawane (Paulus Civil Engineering Journal, 2022)
Many transportation infrastructures, namely roads, have been damaged in Indonesia, one of the causes is the asphalt compaction process that is not in accordance with the temperature in the field, so a test is needed on variations in collision temperature. Seriti has a source of material in the form of river stone and has met the 2018 Bina Marga Standard (Parerung, 2020), so the material from the Seriti river is very suitable for reuse in this study. The methodology in this study is the Conventional Marshall test to obtain the optimum temperature and Marshall Immersion test to obtain Marshall Residual Stability (SMS)/Durability. This study used a mixture of AC-Base with variations in compaction temperature 90℃, 100℃,110℃,120℃ and 130℃ and asphalt content of 4.5%. Based on the results of the analysis of the variation of compaction temperature 90℃, 100℃,110℃,120℃ and 130℃ obtained stability value 2315,7 kg, Flow 4,20 mm, VIM 3,14%, VMA 13.95% and FVB 75, 57%. Based on the results of this research, it can be concluded that the optimum temperature obtained is 130℃ which meets the 2018 Highways Specifications.